Experimental and numerical investigation on bare tube cross flow heat exchanger-using COMSOL. Issue 5 (15th April 2020) - Meikandan, M.; Sundarraj, M.; Yogaraj, D.; Malarmohan, K.
ABSTRACT: In this study, COMSOL multi-physics modelling software was used to make a computational model of a bare helical tube cross flow heat exchanger in order to simulate the temperature changes in the heat exchanger. The computational results of heat transfer are validated by using the analytical models. A conjugate convection/conduction heat transfer model was developed, which exhibited good agreement to the experiments. A different velocity of air taken into the consideration to find out the temperature distribution through the pipe and air temperature inside the duct. The temperature profile, and the overall heat transfer rate from the wall of the tube were calculated and plotted for theoretical, experimental and Numerical method using the k- conjugate heat transfer model. The model is validated through comparison with theoretical relations for single-pass cross-flow arrangements and with experimental results also. Simulation results showed good agreement with experimental values with respect to different mass flow rates.